Models clarify Tahoe clarity loss - R Meadows (California Agriculture, 2006)
Tahoe is one of the most beautiful lakes in the world, with such clear blue water that you could once see to depths of more than 100 feet. But Lake Tahoe's extraordinary clarity has declined for half a century and today you can usually only see to depths of about 70 feet.